Model of Customer Satisfaction and Loyality - Segoro, Waseso; Limakrisna, Nandan (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT This study presents an empirical model of service quality and appropriate relationality for cellular operators, so that service users can achieve high satisfaction and loyalty. This occurs at the level of the prices offered for the lower middle segment, as well as at the level of quality for the upper middle segment. The method used is the descriptive and verification survey. The sample consists of 285 students in the third semester of eight tertiary institutions. To measure all the constructions and indicators a research questionnaire was used and the method of data analysis was SEM (Structural equation modeling).